Biomolecular markers in assessment and treatment of asthma. Issue 4 (3rd April 2014) - Fatemi, Farnaz; Sadroddiny, Esmaeil; Gheibi, Azam; Mohammadi Farsani, Taiebeh; Kardar, Gholam Ali
Abstract Asthma is a chronic and heterogeneous inflammatory disorder with several different phenotypes. Whereas clinical features of asthma are non‐specific and pulmonary function tests are often insensitive, further development is needed for efficient treatment or even early diagnosis. Recently, several airway inflammatory biomarkers have emerged as valuable tools in diagnosis and management of asthma. The analysis of molecular markers of airways inflammation has provided promising and non‐invasive techniques that facilitate the detection of disease phenotypes as well as measurement of therapeutic efficacy. Although conventional treatments remain the preferred therapy, they do not adequately control some severe cases of asthma. Novel therapeutic agents have been developed to target various biomarkers involved in the inflammatory responses and have been investigated in patients with asthma. In this article, we summarized the most studied asthma biomarkers, derived from a variety of biological sources including exhaled gases, induced sputum, serum and urine. Likewise, the effects of current anti‐inflammatory asthma treatments on inflammatory biomarkers and some promising biomarkers for developing new targeted therapies are also discussed.